Women's Entrepreneurship in Europe Multidimensional Research and Case Study Insights (FGF Studies in Small Business and Entrepreneurship,, 2018)
This volume addresses the current challenges for and future prospects of women's entrepreneurship research, bringing together a wealth of diverse insights with implications for research, education and practice alike. Presenting theoretical and empirical research papers and case studies, the book not only offers a topical reference guide for entrepreneurship researchers and educators, but also provides essential reading material for students interested in questions addressing diverse aspects of the challenges to and future academic and practical prospects of women's entrepreneurship.